Calidad de materiales de envase y empaque utilizados para el acondicionamiento de Meropenem 500mg P.P.S. en una Industria Farmacéutica, Lima 2018 - Calderón Piminchumo, Dennis Alberto (2019)
In this report, the quality of the packaging materials used for conditioning Meropenem 500mg powder for injectable suspension (PPS) in a Pharmaceutical Industry was determined during the year 2018. A batch of packaging and packaging materials was evaluated as vials, plugs, seals, boxes and inserts, for this the tables of Simple Sampling Plans for Normal Inspection and acceptable quality levels (AQL) were used. The search for possible defects was carried out throughout the inspection process, sampling, and analysis of such materials; this was determined by the classification of standardized defects in the industry (critical defect, major or minor). The methodology was based on the realization of physicochemical tests for corks, vials according to American Pharmacopoeia USP41-NF36 and also evaluated by tests by attributes the quality of the mediate container (box), seals and inserts, according to the laboratory's own technique. In conclusion, the quality of the packaging materials meet all the technical specifications for conditioning Meropenem 500mg P.P.S. ; The quality of the immediate glass container (vial) and caps were according to American Pharmacopoeia USP41-NF36 and the quality of the mediated container (box), seals and inserts were according to the laboratory's own technique